Integrating Islam on geometry student worksheets to facilitate mathematical and religious literacy of junior high school students - Masamah, Ulfa; Zain, Nurmalia Khoirunisa; Salsabila, Anisah; Maulidani, Muhammad (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2023)
This study aims to analyze the validity level, practicality level, effectiveness and influence of the Islamic integrated Geometry Student worksheet on mathematical literacy and religious literacy of junior high school students. The research method used in this study is Research and Development with the ADDIE development design, namely Analyze, Design, Development, Implementation, and Evaluation. The subject of the product assessment for the feasibility of the Islamic Integrated Geometry Student Worksheet (students worksheets) is limited to four experts: learning and language design experts, media and graphic design experts, mathematics materials experts and Islamic integration, as well as school mathematics teaching practitioners. The subjects related to the product trial were all class VIII MTs Surya Buana Malang City students. The research instruments used were interview guidelines, validation sheets, observation sheets, student and teacher response questionnaires, mathematical literacy tests, and religious literacy questionnaires. Qualitative data analysis was carried out according to Miles & Hubberman's steps, including data reduction, data display, and conclusion. Quantitative data in validity and practicality are presented as percentages and categories. This research produces a product in the form of an Islamic integrated geometry student worksheet. The validation results show that the Islamic Integrated Geometry Student Worksheet meets the valid criteria of 89.21%. Student responses showed that the Islamic integrated student worksheet product was very practical, with a percentage of 86.56%. At the same time, the teacher assessed that this student's worksheets were very practical, with a percentage of 86.67%. The results of the effectiveness test obtained an average of 85.68%, while the results of the t-test from the pretest and posttest obtained a Sig value. 0.001 and a Sig value of 0.004 for religious literacy. Thus, there is a significant difference between before and after using the Islamic Integrated geometry student worksheet on students' mathematical and religious literacy.